EFFECT OF PECTIN AND PECTIN-CONTAINING PRODUCTS ON THE FUNCTIONAL AND METABOLIC CHANGES OF BONE TISSUE UNDER MODELED OSTEOPOROSIS AND CHRONIC SODIUM NITRATE INTOXICATION - Sorokin, B.V.; Kostenko, V.O. (World of Medicine and Biology, 2013)
The experiment which involved 20 Wistar white rats weighed 180-230 g was aimed to study the effect of pectin and pectin-containing products on the functional and metabolic changes in bone tissue of different skeletal areas (tibia, vertebrae) in modeled osteoporosis and excess production of sodium nitrate induced exogenously (model of chronic sodium nitrate intoxication). It has been found out the introduction of apple pectin under these conditions limits collagenolysis (in tissues of tibia and vertebrae) and proteoglycans depolymerization (in tissues of tibia), increases the density and strength of the tibia. Adding of pectin-containing oatmeal flour to the rats’ diet limits collagenolysis and proteoglycans depolymerization in the tibial tissue, increases their strength properties, but does not significantly affect the functional and metabolic characteristics of the vertebrae.